2016
DOI: 10.1177/1934578x1601100302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three Centaurea Species Collected from Central Anatolia Region of Turkey on Human Melanoma Cells

Abstract: Centaurea is the largest genus within the Asteraceae family. Many members of this genus are used in traditional folk medicine, such as Centaurea pulchella used to treat skin problems such as to resolve the abscess. Although biological activities of many Centaurea species have been investigated in different countries and Turkey, cytotoxic effect of C. patula, C. pulchella and C. tchihatcheffii has not been studied yet. Melanoma is one of the most invasive and deadly forms of skin cancer. Therefore, in an ongoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Other relevant reports revealed that the chloroform and ethyl acetate fractions of C. bruguierana subsp. Belangerana exhibit a potent cytotoxic effect against K562, AGS, MCF-7 and SW742 [ 33 ]. The extracts of C. hermannii have been reported to possess antiproliferative effects against HeLa cancer cells that are associated with induction of apoptosis and necrosis via the engagement of caspases 3, 7 and 9 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other relevant reports revealed that the chloroform and ethyl acetate fractions of C. bruguierana subsp. Belangerana exhibit a potent cytotoxic effect against K562, AGS, MCF-7 and SW742 [ 33 ]. The extracts of C. hermannii have been reported to possess antiproliferative effects against HeLa cancer cells that are associated with induction of apoptosis and necrosis via the engagement of caspases 3, 7 and 9 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%